DNA Barcoding of Cacao Pod Rot Fungi in Papua Province - Gunaedi, Tri; Tanjung, Rosye H.R.; Manwan, Sri Wahyuni (East Asian Journal of Multidisciplinary Research, 2024)
Cocoa (Theobroma cacao) pod rot fungi  have various types. In general, cause cocoa pod rot  are fungi of the species Fusarium sp, Rhizoctonia sp, Phytium sp, Colletotricum sp, Amerosporium sp, Phomopsis sp and Phytopthora sp. Various species of fungi that can rot cocoa pods have high similarity in morphology characters even though the treatment for each species of fungi is different. This problem occurs in the people's nucleus cocoa plantations in the Yapsi district, Jayapura, Papua province. Samples of cacao pods infected with the fungus were taken and the isolates obtained were reinoculated into uninfected cacao pods. Isolates showing dominant infectivity were taken and identified molecularly. Identification was carried out by creating DNA barcoding by sequencing the Internal Transcribed Spacer (ITS) region of the 18SrDNA marker gene from the fungal isolates SP4DYAPSI-1, SP4 DYAPSI-2, SP3DYAPSI-1 and SP6DAUN3. Sequencing data in the form of isolate fungi DNA barcodes were analyzed with the ClustalX program analyses. The resulting phylogenetic tree construction shows that the four isolates are related to the fungus species Fusarium solani with a nucleotide similarity index above 95%. This shows that the cause of damage to cocoa pods in the Yapsi area, Jayapura, Papua, Indonesia is the fungus Fusarium solani.